Primary care providers' responses to pregnancy intention screening challenges: community-based participatory research at an urban community health centre. (11th June 2019) - Srinivasulu, Silpa; Falletta, Katherine A; Bermudez, Dayana; Almonte, Yolyn; Baum, Rachel; Coriano, Madeline; Grosso, Ashley; Iglehart, Kathryn; Mota, Cathy; Rodriguez, Laura; Taveras, Jecenia; Tobier, Natalie; et al.
Abstract: Background: Incorporating pregnancy intention screening into primary care to address unmet preconception and contraception needs may improve delivery of family planning services. A notable research gap exists regarding providers' experiences conducting this screening in primary care. Objective: To explore primary care providers' perceived challenges in conducting pregnancy intention screening with women of reproductive age and to identify strategies to discuss this in primary care settings. Methods: This qualitative study emerged from a 2017 community-based participatory research project. We conducted semi-structured, in-depth interviews with 10 primary care providers who care for women of reproductive age at an urban federally qualified health centre. Analysis consisted of interview debriefing, transcript coding and content analysis with the Community Advisory Board. Results: Across departments, respondents acknowledged difficulties conducting pregnancy intention screening and identified strategies for working with patients' individual readiness to discuss pregnancy intention. Strategies included: linking patients' health concerns with sexual and reproductive health, applying a shared decision-making model to all patient–provider interactions, practicing goal setting and motivational interviewing, fostering non-judgmental relationships and introducing pregnancy intention in one visit but following up at later times when more relevant for patients. Conclusions: Opportunities exist for health centres to address pregnancy intention screening challenges, such as implementing routine screening and waiting room tools to foster provider and patient agency and sharing best practices with providers across departments by facilitating comprehensive training and periodic check-ins. Exploring providers' experiences may assist health centres in improving pregnancy intention screening in the primary care setting.